ANALISIS NILAI CINTA TANAH AIR DALAM PENGGUNAAN MEDIA PAPAN KANTONG KELAS V - Arfianti, Sindi; Asriyanti, Frita Devi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The abstract concept of national values is difficult for students who are still at the concrete operational stage of thinking to understand, so interactive and contextual learning media such as pocket board. This study aims to describe the value of patriotism through the use of the pocket board as a teaching aid for fifth-grade students. This study employs a descriptive qualitative approach. The research subjects consisted of 21 fifth-grade students and their classroom teacher. Data were collected through direct observation during the learning process, structured and in-depth interviews, and document analysis. Data analysis was conducted in three stages: data reduction, data presentation, and drawing conclusions. Data validity was ensured through triangulation. The results of the study indicate that the use of the pocket board teaching aid significantly supports the instillation of patriotism in fifth-grade students. Based on the observation results, a total score of 734 was obtained, with an average score of 34.95 and a success rate of 87.34%, placing it in the “very high” category. This sense of patriotism is reflected in the students’ concrete behaviors, such as (1) taking pride in being Indonesian citizens; (2) appreciating cultural diversity and domestic products; (3) maintaining the cleanliness and sustainability of the school environment; (4) complying with school rules and regulations; and (5) respecting differences in background among classmates. The pocket board is highly recommended as an applicable alternative learning medium for elementary school teachers to help students internalize national character values.